INFLUENCE OF RETIREMENT PLAN ON PERCEIVED RETIREMENT ANXIETY AMONG STAFF IN USMANU DANFODIYO UNIVERSITY SOKOTO, NIGERIA: IMPLICATIONS FOR CAREER COUNSELLING - Shehu Yahaya Tsagem PhD; Abdullahi, Rukayya, (EPRA International Journal of Research and Development (IJRD), 2023)
Retirement is an inevitable phase of life that all those engaged in paid labour have to face at a certain time, as such planning for it should be unavoidable also. Many times, workers experience fears when approaching retirement period for the simple reason that they did not plan for it; workers in Usmanu Danfodiyo University are not any different. Thus, the study investigated how retirement planning influenced retirement anxiety among the staff. Using descriptive survey, the study utilizes purposely sampled staff who retired and those who are about to (N = 31). An adapted version of Preretirement Planning Questionnaire was used to collect data, which was analyzed by using chi-square and independent t-test analysis. Results indicated that planning for retirement positively influence retirement anxiety among the staff, and also that there was no difference in how the academic staff plan for retirement or how they experienced anxiety over retirement from that of the non-academic staff. Among the recommendations made was that employees in the university should plan ahead for the inevitable date of their retirements; in this way they would greatly reduce or altogether avoid feelings of concerns that may be a source of anxiety. One of the implications for career counselling is to employ adequate counselling approaches so that employees in the university should be empowered to plan ahead for the inevitable date of their retirements; in this way they would greatly reduce or altogether avoid feelings of concerns that may be a source of anxiety.